Impact of Temperature on the Rate of Chemical Reactions in Tanzania - Matata, Susan (European Journal of Physical Sciences, 2024)
Purpose: The aim of the study was to assess the impact of temperature on the rate of chemical reactions in Tanzania. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that as temperature increases, the kinetic energy of the molecules involved in a reaction also rises. This elevation in kinetic energy results in more frequent and forceful collisions between reactant molecules, thus increasing the likelihood of successful interactions that lead to the formation of products. The relationship between temperature and reaction rate is quantitatively described by the Arrhenius equation, which demonstrates that even a small increase in temperature can lead to a significant rise in the reaction rate. Additionally, higher temperatures can help overcome activation energy barriers more effectively, enabling reactants to convert into products at a faster pace. However, it is important to note that extremely high temperatures might also cause the decomposition of reactants or the denaturation of catalysts, potentially inhibiting the reaction. Implications to Theory, Practice and Policy: Arrhenius equation theory, transition state theory and collision theory may be used to anchor future studies on assessing the impact of temperature on the rate of chemical reactions in Tanzania. Based on the findings of studies like Chen & Zhang (2021), there is a clear need for advanced, responsive temperature control systems in chemical manufacturing. Policymakers should consider establishing guidelines and regulations that define safe and effective temperature ranges for various industrial processes, particularly those involving hazardous materials.